Pendidikan Karakter Berkearifan Lokal Bugis: Telaah Epistemologi Pemikiran Nene Mallomo - Nurmiati; Asrul Muslim; Syahril (Jurusan Tarbiyah STAI Al-Gazali Bone, 2026)
This research article focuses on studying character education with Bugis local wisdom through an epistemological review of Nene Mallomo's thoughts. Through library research, it was found that Nene Mallomo's ideas about character traits like macca, malempu, warani, and magetteng can be developed through life experiences, observation of social reality, tradition and culture, as well as reflection on various life events. Experiences teach individuals to learn from successes and failures, shaping thinking skills, honesty, courage, and firmness of principles. Social observation allows learning from the behavior and experiences of others, including in solving problems and facing moral consequences. Traditions and culture pass down these values as part of Bugis community life. Next, reflection involves processing experiences, observations, and traditions into moral awareness, wisdom, and guidelines for living life responsibly.